AMETTA LEARNING MODEL DESIGN (ACTIVE, FUN AND WITHOUT PRESSURE) - Yenni Hasnah; Pirman Ginting; Ratna Sari Dewi (JURNAL TARBIYAH, 2020)
This study aims to design a learning model that is active, fun, and without pressure called the AMETTA learning model. Research activities are carried out by applying a mixed research method that combines qualitative and quantitative data analysis with the stages of research activities, including literature studies, field studies, data collection, data analysis, and designing learning models. The results show that the AMETTA learning model design is suitable for use as a learning model to improve learning quality based on experts' feedback. This feasibility is also supported by an increase in the percentage of students' learning success, which is significant between the initial and final tests on small-scale (34.28%) and large-scale (38.47%) trials that this learning model is useful for implementation in learning activities. The AMETTA learning model meant is active, fun, and stress-free learning through the application of varied and exciting learning methods and media and the implementation of the Brain Gym in the learning process.